emoval of malachite green dye from aqueous solutions by diasporic Greek raw bauxite - Georgiadis, I.K.; Papadopoulos, A.; Filippidis, A.; Godelitsas, A.; Tsirambides, A.; Vogiatzis, D. (Bulletin of the Geological Society of Greece, 2013)
Raw bauxite from Klisoura mine (Prefecture of Fokida, Greece) containing 72 wt.% diaspore, 16 wt.% hematite, 6 wt.% quartz, 4 wt.% anatase and 2 wt.% calcite, has been used for the removal of malachite green dye from aqueous solutions. The batch type experiments were conducted with 10 ml of solution, at pH = pHZPC = 6.7 and contact time 1 h. The initial concentration of malachite green dye was 10 mg/l, the bauxite quantity was 0.02 g, 0.04 g, 0.06 g, 0.1 g and 0.2 g. The highest adsorption capacity achieved was 4.5 mg/g (90% removal) using 0.02 g bauxite. The removal capacity of raw bauxite is comparable to other non-conventional adsorbents, such as neem sawdust, sugar cane dust and cane root carbon.